Demographic and Regional Labour Market Analysis of the Historic Market Towns of Greater Cumania, Hungary - Mezei, Martin; Nagyné Molnár, Melinda (Studia Mundi – Economica, 2024)
The subject of my research is the study of the settlements with a rural-urban past in the Greater Cumania (Hungarian name of the region: Nagykunság). This historic small region in the Northern Great Plain region is a region with many economic and social problems. My research covers six settlements, all of which have a rural-urban past, but only five of them have city status today: Karcag, Kisújszállás Kunhegyes, Kunszentmárton and Túrkeve. Kunmadaras is a municipality.The focus of my research is on the common economic and cultural heritage of these settlements and their unique development paths. The common economic and cultural heritage is the past as a field town, and the heritage that the Kuns who founded the settlements not only had an administration independent of the county system, a patent status, but also shared a common culture. Grater Cumania as a historical region is no longer a functional unit. Starting from common foundations, the six settlements have responded differently to the challenges of the past decades. The extent to which each of them has successfully responded to the economic and social challenges they have faced is faithfully reflected in their economic and social relations.The aim of my research is, on the one hand, to review the current balance of the settlements with a rural-urban past in Greater Cumania, both individually and in comparison with each other, in order to identify future opportunities, possibilities and threats. On the other hand, my aim is also to examine what the common Greater Cumanian heritage means for the settlements that have taken different development paths and rely on different spatial relations. Can a cultural product, a brand, be built out of it?
Keywords: labour market; demography; territorial disparities